Case report: ‘Photodynamics of Subependymal Giant Cell Astrocytoma with 5-Aminolevulinic acid’ - Ghani, Imran; Patel, Sabina; Ghimire, Prajwal; Bodi, Istvan; Bhangoo, Ranjeev; Vergani, Francesco; Ashkan, Keyoumars; Lavrador, Jose Pedro (Frontiers in Surgery, 2023)
Subependymal Giant Cell Astrocytoma (SEGA) is a common diagnosis in patients with Tuberous Sclerosis. Although surgical treatment is often required, resection may entail a significant risk for cognitive function given the anatomical relation with critical structures such as the fornices and subgenual area. Therefore, target subtotal resections using minimal invasive approaches focused in the higher metabolic areas are valuable options to preserve quality of life while addressing specific problems caused by the tumor, such as hydrocephalus or progressive growth of a specific component of the tumor. In this report, the authors explore the potential role of 5-ALA in the identification of highly metabolic areas during SEGA resection in the context of minimal invasive approaches.